2013
DOI: 10.1371/journal.pone.0062227
|View full text |Cite
|
Sign up to set email alerts
|

Productive Infection of Bovine Papillomavirus Type 2 in the Urothelial Cells of Naturally Occurring Urinary Bladder Tumors in Cattle and Water Buffaloes

Abstract: BackgroundPapillomaviruses (PVs) are highly epitheliotropic as they usually establish productive infections within squamous epithelia of the skin, the anogenital tract and the oral cavity. In this study, early (E) and late (L) protein expression of bovine papillomavirus type 2 (BPV-2) in the urothelium of the urinary bladder is described in cows and water buffaloes suffering from naturally occurring papillomavirus-associated urothelial bladder tumors.Methods and FindingsE5 protein, the major oncoprotein of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 39 publications
3
30
0
Order By: Relevance
“…The histopathological findings of the samples are consistent with those lesions typically observed in papilloma lesions [17,24,25] but no fibroblast proliferation was observed, ergo clinical and histopathological findings confirmed the diagnosis of papillomatosis. The majority of the strains clustered within the Deltapapillomavirus genus that encompasses the BPV types considered to be etiological agents of papillomatosis in cattle [12,13,17,18], sarcoid disease in horses [4,5,26], as well as urinary bladder in cow [27]. BPVs 1 and 2 are the most common BPV types distributed worldwide and unusually, they have the ability to infect not only bovines but also other species such as equines [4,5,26], yaks [28], and buffalos [27,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The histopathological findings of the samples are consistent with those lesions typically observed in papilloma lesions [17,24,25] but no fibroblast proliferation was observed, ergo clinical and histopathological findings confirmed the diagnosis of papillomatosis. The majority of the strains clustered within the Deltapapillomavirus genus that encompasses the BPV types considered to be etiological agents of papillomatosis in cattle [12,13,17,18], sarcoid disease in horses [4,5,26], as well as urinary bladder in cow [27]. BPVs 1 and 2 are the most common BPV types distributed worldwide and unusually, they have the ability to infect not only bovines but also other species such as equines [4,5,26], yaks [28], and buffalos [27,29].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the strains clustered within the Deltapapillomavirus genus that encompasses the BPV types considered to be etiological agents of papillomatosis in cattle [12,13,17,18], sarcoid disease in horses [4,5,26], as well as urinary bladder in cow [27]. BPVs 1 and 2 are the most common BPV types distributed worldwide and unusually, they have the ability to infect not only bovines but also other species such as equines [4,5,26], yaks [28], and buffalos [27,29]. In Brazil, these BPV types were already described in studies carried out in cattle herds from the Southern, South-East and North-East regions [13,18,30,31], and the present findings reveals that they are also present in the Amazon region of Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that papillomavirus L1 protein plays a central role both in infection and immunogenicity [44]. It has just been shown that L1 protein is surprisingly expressed in high-grade bladder cancer of ruminants [45]. L1 protein expression may contribute to chronic inflammation of tumor stroma known to have an important role in the progression and metastasis of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Bladder carcinomas are relatively common in cattle grazing on bracken fern in synergy with BPV1 and BPV2 (Roperto et al., ; Roperto, Russo, Ozkul, Corteggio, et al., ; Roperto, Russo, Sepici‐Dincel, et al., ; Wosiacki, Reis, Alfieri, & Alfieri, ). They were also detected in buffaloes and yaks, although sporadically (Roperto, Russo, Ozkul, Corteggio, et al., ; Roperto, Russo, Sepici‐Dincel, et al., ).…”
Section: Papillomavirus Diseasesmentioning
confidence: 99%